A Socioecological Model of Risk Associated With Campus Sexual Assault in a Representative Sample of Liberal Arts College Students - Herres, Joanna (Journal of interpersonal violence, 2021)
Campus sexual assault (CSA) is a growing area of research and public health concern, yet little research has considered the sociocultural context in which CSA occurs or the effect of sociocultural factors on the posttraumatic stress disorder (PTSD) symptoms of CSA survivors. This study describes the results of a web-based census survey administered to students at a liberal arts college. Of the 1,611 students who completed the survey (74% female; 71.4% White, 4.3% African American, 12% Hispanic), 13.5% reported experiencing at least one type of completed or attempted CSA. Female students, participants in Greek life, and students who reported victimization prior to college were more likely to report having experienced CSA. CSA was positively correlated with PTSD symptoms, and this relationship was stronger for racial/ethnic minorities, those who reported less sense of community, and those who were more aware of campus services to address CSA. This study demonstrates multiple levels of sociocultural influence on the mental health of college students who have experienced CSA and may suggest ways for improving prevention and intervention strategies to address CSA and its consequences.